Milk quality and safety issues inside the farm gate of dairy farmers of Punjab (India) - Singh, Harmandeep; Singh, Jaswinder; Verma, Harish Kumar; Kansal, Suresh Kumar (Indian Journal of Dairy Science, 2020)
Milk quality and safety is the biggest concern of the Indians’ dairy industry. Although milk contamination can occur at any stage of the milk value chain but farm contamination is supposed to be the major culprit. The present study investigated the perception and practices of dairy farmers about milk safety and quality at the farm level. Randomly selected dairy farmers (n -300), across the five different agro-climatic zones of Punjab, India, were surveyed using a pre-tested structured questionnaire. The study analyzed the awareness and practices of the respondents based on the five aspects namely milker’s hygiene, animal hygiene, environmental hygiene, milk handling, and chemical residue in milk. Pooled milk samples collected from every alternate farm (n-150) were subjected to somatic cell count (SCC), fat, SNF, adulteration, and E.Coli contamination. Â Data were analyzed using SPSS software through descriptive statistics, Chi-square test of independence with Cramerâ€™s V value as measures of effect size. Analysis of variances, followed by Games Howell post hoc test was performed to analyze subgroup differences amongst explanatory variables. Â The majority of farmers (64%) were found to have low knowledge scores related to all five aspects of milk quality and safety. The milk handling (ranked first) followed by animal hygiene, personal hygiene, environmental hygiene, and antibiotics and other residues in milk (ranked last)Â ordered wise aspects affecting milk quality and safety. Further, socio-demographic and farm characteristics of respondents have a positive influence on the farmer’s knowledge of milk quality and safety. High SCC (Mean- 424000) and E .coli contamination in 24% samples further revealed poor adherence to hygienic milk practices. Only 5% of samples were found adulterated with water and 3% of samples were found to be urea positive. Â Ignorance and lack of scientific knowledge among dairy farmers are the major hindrances in the production of quality and safe milk. An extensive awareness program on milk quality and safety, coupled with incentives on quality products should be undertaken to enhance the awareness of the small and medium dairy farmers.